Energy efficient cluster-based routing protocol using leach and charged system search algorithm in WSN - Nandhini, P.; Suresh, A. (International Journal of Engineering and Technology, 2019)
There are several sensor nodes in a wireless sensor network (WSN). Their energy, storage and processing abilities are constrained. One important task associated with the sensor nodes is to gather the data and relay it to the base station (BS). Thus, for designing effective data collection techniques in WSN, the critical factor is the network lifespan. This is because every sensor node has restricted energy resource. The literature presents a scheme for data collection based on clustering which can effectively save energy .The Low Energy Adaptive Clustering Hierarchy (LEACH) protocol is used for accumulating clusters and changing CH positions so that the energy is uniformly disseminated throughout the nodes. The literature specifies that the design of an energy-balanced clustering for peak network lifespan of WSN is a Non-deterministic Polynomial (NP)-hard problem. In the recent past, several meta-heuristic approaches on which the clustering schemes are based have been suggested for solving the NP-hard problem. Nonetheless, these clustering schemes suffer from uneven consumption of power. This research suggests an optimized Cluster Head (CH) selection algorithm that makes use of Charged System Search (CSS), for solving the aforementioned issue. It has been shown via empirical outcomes that compared to LEACH (Low-Energy Adaptive Clustering Hierarchy) protocol, this suggested scheme provides better throughput. Thus the suggested CSS optimized CH selection is promising for extending the network lifespan.